Review: The Consumption of Ultra-Processed Foods and Non-communicable Diseases in Latin America - Matos, Rodrigo A.; Adams, Michelle; Sabaté, Joan (Frontiers in Nutrition, 2021)
The objective of this article is to assess current trends in Latin America with respect to the consumption of ultra-processed foods and non-communicable diseases. This review addresses the rapid growth of the ultra-processed foods market in Latin America which, along with other social and environmental factors, has been shown to be highly influential in the prevalence of non-communicable diseases such as obesity, type 2 diabetes, hypertension and cardiovascular disease, cancer, and all-cause mortality. Ultra-processed foods represent a health concern for a number of reasons. They are generally calorically dense and high in sodium, sugar, and saturated and trans fats, and low in fiber and protein. Additionally, they may contain additives and neoformed compounds that affect health in ways that have not been adequately researched. Furthermore, the packaging of ultra-processed foods may contain hormone disruptors whose effects on humans are not entirely clear. Associations between ultra-processed foods and cardio-metabolic dysfunction, as well as several plausible mechanisms, will be evaluated